Implementasi Kebijakan City Branding Madiun Kota Pendekar dan Dampaknya bagi Kota Madiun - Sunarso, Sunarso; Halim, Abdul; Puspadyna Bilyastuti, Mai; Kristanti Setyaningtyas, Ester (Universitas Indo Global Mandiri, 2023)
This study aims to find out how the strategy for implementing the city branding policy for Madiun, the City of Pendekar and its impact on the City of Madiun. This type of research is descriptive qualitative with a case study approach. Data collection techniques were carried out through observation techniques, in-depth interviews and documentation studies. Then for data analysis, the researcher did it in the following stages: (a) data collection; (b) data assessment; (c) data interpretation; and (d) data inference. The results showed that the implementation of the city branding policy for Madiun City Pendekar was well implemented through several program strategies, namely: 1) making the Madiun City Pendekar logo and clothing; 2) identity development through warrior statues; 3) Development of the Pencak Silat Gallery; 4) the Friends of Pencak Silat program; 5) organizing pencak silat events; and 6) empowering youth communities and the creative economy. The city branding policy of Madiun City of Pendekar has had a positive impact, namely improving communication between silat schools, increasing security and public order, and providing support for city tour policies. However, this positive impact is considered not optimal because clashes or brawls between silat schools still occur at low intensity.